Training Effect on Speech Rhythm of Nepalese Non-Native Speakers of English - Aryal, Ananda (Journal of NELTA, 2015)
This project aimed to ascertain the effect of training on speech rhythm of Nepalese non-native speakers of English. Six Nepalese and one native speaker of English participated in this research. A six-week training program was administrated and pre- and post-training guided speech samples were acoustically analysed. Acoustic measurement of the pre- and post-training speech samples showed that training played an important role in improving the rhythm of Nepalese non-native speakers of English. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12077 Journal of NELTA, Vol 19 No. 1-2, December 2014: 17-31